OcculterCut: A comprehensive survey of AT-rich regions in fungal genomes. - Renwick, Alison; Oliver, Richard; Hane, James (Oxford University Press, 2016)
We present a novel method to measure the local GC-content bias in genomes and a survey of published fungal species. The method, enacted as "OcculterCut" (https://sourceforge.net/projects/occultercut), identified species containing distinct AT-rich regions. In most fungal taxa, AT-rich regions are a signature of repeat-induced point mutation (RIP), which targets repetitive DNA and decreases GC-content though the conversion of cytosine to thymine bases. RIP has in turn been identified as a driver of fungal genome evolution, as RIP mutations can also occur in single-copy genes neighbouring repeat-rich regions. Over time RIP perpetuates 'two speeds' of gene evolution in the GC-equilibrated and AT-rich regions of fungal genomes. In this study, genomes showing evidence of this process are found to be common, particularly among the Pezizomycotina. Further analysis highlighted differences in amino acid composition and putative functions of genes from these regions, supporting the hypothesis that these regions play an important role in fungal evolution. OcculterCut can also be used to identify genes undergoing RIP-assisted diversifying selection, such as small, secreted effector proteins that mediate host-microbe disease interactions.